Historical references to Marudham - A, Rajalakshmi (Indian Journal of Tamil, 2020)
The main characteristic of The Sangam literature is the five types of lands captive kurinji, mullai, marudham, neithal and palai, and the adjoining people sects, the customs and disciplines shown by the department. There are many reports of the ethics and customs that arose in the prehistory of the state and that the state was not the state. The article deals with the Marudham historical references spoken in the Akananuru.